Ridin' with the pack : a western short story collection [large type] - Bray, Jake; Brandvold, Peter; Rundell, B. N.; Martin, Larry Jay; Nesbitt, John D.; Mullen, Chris (Novelist); Pratt, Ken (Kenneth S.); Gear, W. Michael (Thorndike Press large print softcover western, 2024)
"From the enigmatic reflections of a down-and-out fella questioning the choices he's made to an action-packed expedition in the wild expanses of the Old West, each story paints a vivid portrait of the American frontier's enduring heart. Readers will navigate the steamy bayou as a determined young man faces unimaginable challenges to rescue a kidnapped friend, experience the seafaring odyssey of a man shanghaied on the eve of his wedding, encounter the convergence of past and present as a young bounty hunter meets his match, traverse a California hitchhiker's fateful choices as they lead him to a dark and unpredictable highway, and join a Wyoming family in the aftermath of a banking system collapse as they fight for their land and heritage amid a new dimension of uncertainty. No matter the story, the spirit of the West is ever-present, each tale unfolding like a chapter in the grand narrative of the untamed frontier-where freedom, resilience, and the relentless pursuit of justice echo like the haunting melodies of a cowboy ballad. Penned by a cadre of masterful storytellers, both seasoned legends and promising newcomers, Ridin' with the Pack is a testament to the timelessness of the Western narrative"--